ICT, e-formalization and tax mobilisation efforts in sub-Saharan Africa - Cyril Chimilila; Vincent Leyaro (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2022)
This paper investigates the effect of ICT and e-formalization on tax mobilization efforts in sub-Saharan Africa. Using a panel of 42 countries from 1991 to 2018 and applying appropriate model specifications; the empirical findings show that there is strong support that ICT (mobile subscription and internet usage) and e-formalization (e-government) enhanced tax mobilization efforts. There is scope to increase tax compliance and expand the tax base in SSA (tax mobilization efforts) through the increase in the usage of ICT that can be applied to simplify tax administration, reduce compliance costs, and provide convenience to taxpayers and enhance enforcement. It is equally important that other policies are skewed toward supporting the development of ICT in SSA countries, supporting the application to improve e-payments, formalization, and tax administration. Furthermore, tax administrations in SSA should take advantage of ICT in discouraging the use of cash in paying taxes to help reduce informality, integrate systems that use third-party information collected from e-payment platforms, and combine advanced data analysis to expand the tax base, enhance enforcement and increase taxpayer compliance.
Keywords: H21; H26; H30; 330; ICT; e-formalization; tax effort; sub-Saharan Africa